2020
DOI: 10.2196/preprints.26022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using the Computer-based Health Evaluation System (CHES) to Support Self-management of Symptoms and Functional Health: Evaluation of Hematological Patient Use of a Web-Based Patient Portal (Preprint)

Abstract: BACKGROUND Patient portals offer the possibility to assess patient-reported outcome measures (PROMs) remotely and first evidence has demonstrated their potential benefits. OBJECTIVE In this study, we evaluated patients’ use of a web-based patient portal where patients can complete PROMs. The portal was developed to supplement routine monitoring at the Department of Internal Medicine V in Innsbr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While we have documented a positive uptake of the use of this platform from the physicians’ standpoint, we cannot speculate on the patients’ perception of using this platform. However, a recent study that specifically examined the value of ePRO collection in the hematologic setting (including 102 patients with multiple myeloma and chronic lymphocytic leukemia) focused on the patients’ perception of the use of the portal and provided some reassuring data ( 19 ). The authors found that the majority of patients (84%) were willing to use the portal; however, they also observed that the completion of ePROs decreased over time, mainly because of the patient’s forgetfulness, and suggested ways to increase long-term participation rates ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While we have documented a positive uptake of the use of this platform from the physicians’ standpoint, we cannot speculate on the patients’ perception of using this platform. However, a recent study that specifically examined the value of ePRO collection in the hematologic setting (including 102 patients with multiple myeloma and chronic lymphocytic leukemia) focused on the patients’ perception of the use of the portal and provided some reassuring data ( 19 ). The authors found that the majority of patients (84%) were willing to use the portal; however, they also observed that the completion of ePROs decreased over time, mainly because of the patient’s forgetfulness, and suggested ways to increase long-term participation rates ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study that specifically examined the value of ePRO collection in the hematologic setting (including 102 patients with multiple myeloma and chronic lymphocytic leukemia) focused on the patients’ perception of the use of the portal and provided some reassuring data ( 19 ). The authors found that the majority of patients (84%) were willing to use the portal; however, they also observed that the completion of ePROs decreased over time, mainly because of the patient’s forgetfulness, and suggested ways to increase long-term participation rates ( 19 ). In another recent study, 227 lymphoma and chronic lymphocytic leukemia patients who completed web-based PRO questionnaires were randomized to care as usual (CAU), or to CAU plus return of PRO results (with or without a web-based self-management intervention) ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed ePROtect based on the computer‐based health evaluation system (CHES) 9,10 as an easy‐to‐use application for patients during cancer therapy. Positive findings and previous experience with CHES in adult cancer populations have been incorporated 11,12 .…”
Section: Methodsmentioning
confidence: 99%